(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was conducted to find out the comparative growth performance of six color mutants Japanese quail in Bangladesh. Under this experiment the mortality had shown no significant differences among different isolated plumage color mutants (p>0.05). At day- old it is clear that day- old weight was superior in BB- Black than other mutants (p<0.05). At 1st week the body weight was higher in BB- Black, intermediate in BB-Dhakaya and BB- Tuxedo and the lowest in BB- White, BB- Fawn and BB- Rosseta (p<0.05). At 2nd and 5th weeks of age no significant differences in body weight was found among 6 different isolated plumage color mutants (p>0.05). At 3rd week the body weight is higher in BB- Rosseta, intermediate in BB- White, BB- Fawn, BB- Dhakaya and BB- Black and the lowest in BB- Tuxedo (p<0.05). At 4th week the body weight was higher in BB- Black and BB- Fawn, intermediate in BB- Rosseta, BB- White and BB- Dhakaya and the lowest in BB- Tuxedo (p<0.05). The body weight at marketing age (6 weeks) was higher in BB- Black than other mutants whereas other mutants had shown lower values except BB- Fawn (p<0.05). So BB-Black mutants quail is the best one for farming of quail in perspective of growth in Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 7-10